Frequent Consumption of Micronutrient-Rich Foods Is Associated With Reduced Risk of Anemia Among Adolescent Girls and Boys in Indonesia: A Cross-Sectional Study. Issue 1 (June 2021) - Knijff, Marthe; Roshita, Airin; Suryantan, Julia; Izwardy, Doddy; Rah, Jee Hyun
Background: Anemia is a global public health concern. Its devastating consequences include impaired cognitive and motor development, reduced work productivity, and adverse birth outcomes, all of which apply to adolescents, as well as adults and children. Objective: This study aimed to examine the determinants of anemia in Indonesian adolescent girls and boys from Klaten and Lombok Barat districts. Methods: A total of 2150 adolescents who participated in a cross-sectional household survey were included in the analysis. The dietary intake of adolescents was assessed using a 7-day food frequency questionnaire. The relationship between anemia status, dietary intake, and other hypothesized determinants was assessed for adolescent girls and boys on a separate basis, using complex samples Cox regression analysis. Variables were selected for inclusion in multivariate models if they were significantly associated with the dependent variable in univariate models ( P < .05). Results: The prevalence of anemia among adolescent girls and boys was 19% and 5%, respectively. In multivariate analyses, frequent consumption of animal-based iron-rich foods was significantly associated with a lower risk of anemia (prevalence ratio [PR]: 0.59; 95% CI: 0.36-0.97) among adolescent girls, whereas a higher intake of vitamin A-rich fruits and vegetables was associated with a reduced risk of anemia (PR: 0.41; 95% CI: 0.20-0.85) among adolescent boys, after adjustment for all potential confounders. Conclusions: Increased consumption of iron- and vitamin A-rich foods through the implementation of gender-responsive Social Behaviour Change Communication (SBCC) interventions is warranted. This should be coupled with improved coverage and quality of iron and folic acid supplementation programs in adolescents.